2018
DOI: 10.48550/arxiv.1810.10935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convexity of Whitham's highest cusped wave

Alberto Enciso,
Javier Gómez-Serrano,
Bruno Vergara

Abstract: We prove the existence of a periodic traveling wave of extreme form of the Whitham equation that has a convex profile between consecutive stagnation points, at which it is known to feature a cusp of exactly C 1/2 regularity. The convexity of Whitham's highest cusped wave had been conjectured by Ehrnström and Wahlén.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…After this breakthrough work, there have been an increasing number of studies on nonlocal equations using their approach. One of the earliest papers in this direction is to justify the convexity of the wave profile between consecutive crests using a computer-assisted proof [14]. A similar result as in [12] but for solitary waves was also obtained by Truong, Wahlén, and Wheeler [20] using a center manifold theorem approach.…”
Section: Introductionmentioning
confidence: 75%
“…After this breakthrough work, there have been an increasing number of studies on nonlocal equations using their approach. One of the earliest papers in this direction is to justify the convexity of the wave profile between consecutive crests using a computer-assisted proof [14]. A similar result as in [12] but for solitary waves was also obtained by Truong, Wahlén, and Wheeler [20] using a center manifold theorem approach.…”
Section: Introductionmentioning
confidence: 75%
“…Even more, in [10] it was shown that there exist cusped, periodic traveling-wave solutions to the Whitham equation, and that they have exact 1/2-Hölder regularity at crests -corresponding to the order of the dispersion in the equation. It was conjectured that such solutions are convex between cusps, which was confirmed by a computer-assisted proof in [12].…”
Section: Introductionmentioning
confidence: 78%
“…Significant breakthrough in the last decade, however, has put the original Whitham equation, and also other full-dispersion models, in the spotlight, beginning with the existence of periodic traveling waves by Ehrnström and Kalisch [9] in 2009 and solitary-wave solutions by Ehrnström, Groves and Wahlén [8] in 2012; see also [30]. Research has furthermore confirmed Whitham's conjectures for qualitative wave breaking (bounded wave profile with unbounded slope) in finite time [16] and the existence of highest, cusp-like solutions [10,12]-now known to also have a convex profile between the stagnation points [13].…”
Section: Introductionmentioning
confidence: 89%